Integrated Preventive Maintenance Scheduling Model with Redundancy for Cutting Tools on a Single Machine - Tavassoli, L. S.; Sakhavand, N.; Fazeli, S. S. (Engineering, Technology & Applied Science Research, 2020)
In this paper, we present an integrated multi-objective framework of a single machine for a single cutting tool problem. Our maintenance policy is based on performing minimal repairs in case of a minor failure and Preventive Maintenance (PM) to avoid a major failure that results in the replacement of the tool. This framework allows simultaneous optimization of the two conflicting time and cost objectives. A redundant system is proposed as a part of the model to assist the production line under a major failure. In addition, the tool’s preventive maintenance time is synchronized with the completion of the machine tool’s work cycle to reduce the machine’s set-up time. The model was optimized using a customized Non-dominated Sorting Genetic Algorithm (NSGA-II). An experimental study based on real-market data was conducted and the results were compared with the ones obtained from classical methods.